(3EOGQI GdJShjb (B:s (3GdeaGgje , GdJWHjb , JWhQ GdGOGA (B/s - (3GHh GSeGYjd, aDGOs ((3GdbGgQI(B: s (3OGQ GdfNVI GdYQHjI(B, s)
(3JYQja GdJShjb h OQGSI GdJhLjgGJ GdGOGQjI fMhg , GdefJL (B: (3eagheg h Yebg h GJSGYg h eDTQGJ fLGMg , GdfXe GdYedjI dZRh GdGShGb HGdefJLGJ GdLOjOI , GSJQGJjLjGJ GdJShjb WhGd OhQI MjGI GdefJL h fXe JSYjQ GdefJLGJ , fXe Jbjje h JYOjd GdCSYGQ , GdJQhjL (B: (3eagheg h CgOGag h cjajI EYOGOg , GdGYdGf h GdHjY GdTNUj , JfXje GdYdGbI eY efGaP GdJhRjY , GSJQGJjLjI GdJShjb h CKQ GdeQcR GdJfGaSj Ydi GdQHMjI , h GNjQG GdQbGHI Ydi CfTWI GdJShjb(B.s
Keywords: (3COGQI GdeHjYGJs; (3GdGOGQIs; (3GdJShjbs; (3GdJShjb `` GOGQIs